Artificial intelligence foundations : learning from experience - Lowe, Andrew; Lawless, Steve (BCS, The Chartered Institute for IT, 2021)
In alignment with BCS AI Foundation and Essentials certificates, this introductory guide provides the understanding you need to start building artificial intelligence (AI) capability into your organisation.